ANTIBACTERIAL ACTIVITY OF NAMNAM FRUIT JUICE FROM SOUTH KALIMANTAN AGAINST STAPHYLOCOCCUS AUREUS AND ESCHERICHIA COLI - Nurbidayah; Nafila; Amalia, Nurul (Journal of Vocational Health Studies, 2023)
Background: Namnam (Cynometra cauliflora L.) has been reported to contain bioactive compounds that are beneficial as being antifungal, antibacterial, antiviral, and antioxidant. Namnam fruit (Cynometra cauliflora L.) is a herbal plant that has antibacterial properties because it contains chemicals in the form of tannins, saponins, and flavonoids. Purpose: To determine the content of phytochemical compounds contained in them and their activity against Staphylococcus aureus and Eshcerichia coli. Method: The method used in this study was agar diffusion using blank disks and the measurement of the inhibition of the test bacteria. Result: The results showed that Namnam fruit juice (Cynometra cauliflora L.) was proven to contain alkaloids, phenol, flavonoid, and saponin phytochemicals. The results of the inhibition zone measurement for S. aureus bacteria at a 100% concentration showed 6 mm and for E. coli bacteria at a 100% concentration showed 7.33 mm, which means that the inhibition zone of the two bacteria was quite intense. It meant that the higher the concentration, the greater the inhibition zone and the stronger the antibacterial activity produced. Namnam fruit juice activity in inhibiting the growth of E. coli bacteria was more substantial when compared to S. aureus bacteria. Conclusion: The result of this study concluded that Namnam fruit juice had the potential to be an antibacterial agent.